Удосконалення способу охолодження напоїв - Тарасенко, Віра Григорівна; Фучаджи, Наталя Олександрівна; Червоткіна, Олександра Олександрівна; Tarasenko, Vira; Fuchadzhy, Nataliia; Chervotkina, Oleksandra (Мелітополь : ТДАТУ, 2022)
UA: В харчовій промисловості широко застосовуються установки для охолодження, заморожування напівфабрикатів та готової продукції. Прикладами застосування обладнання для охолодження води являються охолодження молока, вина, пива, алкогольних та безалкогольних напоїв, цукеркової маси, ковбасних виробів після термообробки тощо. Стаття присвячена удосконаленню технології охолодження напоїв і наведено варіант вдосконалення способу з використанням плівкового теплообмінника швидкого охолодження для продажу фруктових, овочевих, плодоовочевих соків та інших напоїв таких як пиво, квас, лимонад. EN: In the food industry, installations for cooling, freezing semi-finished products and finished products are widely used. Examples of applications for water cooling equipment are the cooling of milk, wine, beer, alcoholic and non-alcoholic beverages, candy mass, sausages after heat treatment. The article is devoted to the improvement of the beverage cooling technology and a variant of the method improvement using a rapid cooling film heat exchanger for the sale of fruit, vegetable, fruit and vegetable juices and other drinks, such as beer, kvass, lemonade. More and more popular are restaurants and swedish eating places, in which they serve not only hot drinks, such as tea, kava, but also cold drinks, as if cooked in cold drinks for fruit, vegetable and fruit juices and other drinks such as beer, lemon, . At the present time, we are afraid of cycling to reach the end of the creation of the technology of swedish, flow-through cooling of the water. The aim of the article is to improve the method of cooling beverages using rapid temperature reduction of juices, which by introducing new structural elements simplifies the design, eliminates intermediate coolant, increases heat transfer efficiency, increases efficiency and reliability of the installation as a whole, simplifies sanitation . The method of determining the criteria of film heat transfer and the main design parameters of the instantaneous beverage cooler can be used in the design of equipment. An option to improve the method of preparation of beverages for sale using a film evaporator for rapid cooling of fruit, vegetable, fruit and vegetable juices and other beverages such as beer, kvass, lemonade, for example apple juice cooling and instantaneous beverage cooler devices are practical and can be used in production.
Improvement in the way beverages are cooled
Тарасенко В. Г., Фучаджи Н. О., Червоткіна О. О. Удосконалення способу охолодження напоїв. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Мелітополь : ТДАТУ, 2022. Вип. 12. том 1. C. 169-175.
Keywords: спосіб охолодження напоїв; плівковий охолоджувач напоїв; ефективність теплообміну; яблучний сік; method of beverage cooling; film beverage cooler; heat transfer efficiency; apple juice